Commitment of Satellite Cells Expressing the Calcium Channel α2δ1 Subunit to the Muscle Lineage. (29th November 2012) - Tamayo, Tammy; Grajales, Liliana; García, Jesús
Abstract : Satellite cells can maintain or repair muscle because they possess stem cell properties, making them a valuable option for cell therapy. However, cell transplants into skeletal muscle of patients with muscular dystrophy are limited by donor cell attachment, migration, and survival in the host tissue. Cells used for therapy are selected based on specific markers present in the plasma membrane. Although many markers have been identified, there is a need to find a marker that is expressed at different states in satellite cells, activated, quiescent, or differentiated cell. Furthermore, the marker has to be present in human tissue. Recently we reported that the plasma membrane α 2 δ 1 protein is involved in cell attachment and migration in myoblasts. The α 2 δ 1 subunit forms a part of the L-type voltage-dependent calcium channel in adult skeletal muscle. We found that the α 2 δ 1 subunit is expressed in the majority of newly isolated satellite cells and that it appears earlier than the α 1 subunits and at higher levels than the β or γ subunits. We also found that those cells that expressed α 2 δ 1 would differentiate into muscle cells. This evidence indicates that the α 2 δ 1 may be used as a marker of satellite cells that will differentiate into muscle.